A pre-meal of whey proteins induces differential effects on glucose and lipid metabolism in subjects with the metabolic syndrome: a randomised cross-over trial. - Bjørnshave, Ann; Holst, Jens Juul; Hermansen, Kjeld (European Journal of Nutrition, 2019)
Purpose: Postprandial lipaemia (PPL), an independent risk factor for cardiovascular disease, is affected by composition and timing of meals. We evaluated if whey proteins (WP) consumed as a pre-meal before a fat-rich meal reduce postprandial triglyceride (TG) and apolipoprotein B-48 (ApoB-48) responses in subjects with the metabolic syndrome (MeS). Methods: An acute, randomised, cross-over trial was conducted. 20 subjects with MeS consumed a pre-meal of 0, 10 or 20 g WP 15 min prior to a fat-rich meal. The responses of TG and ApoB-48 were assessed. We also analysed postprandial responses of free fatty acids (FFA), glucose, insulin, glucagon, glucagon-like peptide 1 (GLP-1), glucose-dependent insulinotropic peptide (GIP) and paracetamol (reflecting gastric emptying rates). Results: WP pre-meal did not alter the TG or ApoB-48 responses. In contrast, the insulin response was more pronounced after a pre-meal of 20 g WP than with 10 g WP (P = 0.0005) and placebo (P < 0.0001). Likewise, the postprandial glucagon response was greater with a pre-meal of 20 g WP than with 10 g WP (P < 0.0001) and 0 g WP (P < 0.0001). A pre-meal with 20 g of WP generated lower glucose (P = 0.0148) and S-paracetamol responses (P = 0.0003) and a higher GLP-1 response (P = 0.0086) than placebo. However, the pre-meal did not influence responses of GIP, FFA or appetite assessed by a Visual Analog Scale. Conclusions: Consumption of a WP pre-meal prior to a fat-rich meal did not affect TG and chylomicron responses. In contrast, the WP pre-meal stimulates insulin and glucagon secretion and reduces blood glucose as expected, and delays gastric emptying. Consequently, our study points to a differential impact of a WP pre-meal on lipid and glucose metabolism to a fat-rich meal in subjects with MeS.